JORNALISMO DE SERVIÇO: O GÊNERO UTILITÁRIO NA MÍDIA IMPRESSA BRASILEIRA - Vaz, Tyciane Cronemberger Viana (2009)
This research has the purpose to analyze service journalism in two cases of Brazilian print media: the newspaper Folha de São Paulo and the magazine Veja, including the magazine Veja São Paulo. The intention was to understand how service journalism, also named as utilitarian genre or utilitarian species, is present in actual print journalism. Firstly, a bibliographic revision was made on this journalism production mode. Then, an exploratory research was made on the service journalism material, published on the studied objects. Thirdly, a quantitative study was made on formats and types of the utilitarian genre on those media vehicles, in editions selected in the year of 2008. And at last, through semi-open interviews with editors from Veja magazine and Folha de São Paulo, it intended to understand the reasons that subside the editorial decisions on behalf of that journalistic kind. The analysis showed that this journalistic genre has been present since it started to be published, until today. It has been noticed that there are six formats; Marques de Melo had already identified four of them, and two, identified in this research, were considered hybrid genres.(AU)